2017
DOI: 10.1007/s00402-017-2830-8
|View full text |Cite|
|
Sign up to set email alerts
|

Superior biomechanical properties and tying time with the modified Prusik knot and Wittstein suture loop to the Krackow stitch

Abstract: Compared to the Krackow stitch, the modified Prusik knot and Wittstein suture loop had less elongation after cyclic loading and similar ultimate load to failure in this porcine in vitro biomechanical study. Shorter knot tying times were required to complete the modified rolling hitch, modified Prusik knot, and Wittstein suture loop than the Krackow stitch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 21 publications
4
16
4
Order By: Relevance
“…Some previous studies 9, 14,15 reported ultimate failure loads of 330-360 N in both the modified rolling hitch and modified Prusik knot groups; meanwhile, the rupture of sutures at the knot was the failure mode in all specimens in both groups. Similar to previous studies, 9,14,15 the present study found 401 + 27 N and 398 + 44 N ultimate failure loads in the MRS and MPS groups, respectively, and all specimens failed due to sutures broken at the suture knot. Regarding elongation after cyclic loading, however, the experimental results in our study seemed to be higher than those in the previous study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Some previous studies 9, 14,15 reported ultimate failure loads of 330-360 N in both the modified rolling hitch and modified Prusik knot groups; meanwhile, the rupture of sutures at the knot was the failure mode in all specimens in both groups. Similar to previous studies, 9,14,15 the present study found 401 + 27 N and 398 + 44 N ultimate failure loads in the MRS and MPS groups, respectively, and all specimens failed due to sutures broken at the suture knot. Regarding elongation after cyclic loading, however, the experimental results in our study seemed to be higher than those in the previous study.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, FiberWire (Arthrex, Naples, FL) sutures were used, whereas ULTRA-BRAID sutures (Smith & Nephew, MA, USA) were used in the previous study. 9 This study had a number of limitations. First, porcine flexor tendons, instead of human tendons, were used in this biomechanical study.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The aforementioned parameters were set based on previous studies. 2,5,11,14,16,[18][19][20][21] A violet line and two violet marks, respectively, made on the tendon at a point 5 cm from the distal end of the tendon and on both suture limbs where they extend from the tendon, served as indicators for measuring the elongation of each suturetendon construct. Elongation after cyclic loading for each sample was acquired by calculating the difference in distance between the violet line on the tendon and the violet marks on each suture after pretensioning and cyclic loading.…”
Section: Biomechanical Testingmentioning
confidence: 99%